DỰ BÁO THỜI HẠN BẢO VỆ HIỆU QUẢ CHO MỘT SỐ VẬT LIỆU BẢO QUẢN BẰNG PHƯƠNG PHÁP THỬ NGHIỆM GIA TỐC - Chử, Minh Tiến; Nguyễn, Viết Thắng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PREDICTION OF THE EFFECTIVE PROTECTION TIME OF SOME PRESERVATIVE MATERIALS BY ACCELERATED TESTS In the article the standard ГОСТ PB 9.513 and some accelerated tests (moist heat test, salt blind test, immersion in artificial sea water, SO2 environment and ability to push HBr tests) are used for calculating effective protection time of some preservative materials including VN.PVK, VN.K17, VN.BO and imported PVK. The obtained protection order for the materials is VN.BO < VN.K17 < VN.PVK < imported PVK, which is quite suitable with practical use. The method is useful for predicting effective protection times of preservative materials.